Designing for Mind: The Role of Psychology in Retail Interior - Kanak Agrawal; Deepti Pande Rana; Pooja Singh (International Journal of Urban Design and Development, 2024)
This research paper investigates the critical role of psychology in retail interior design and its influence on consumer behavior and experience. Through an analysis of psychological principles such as store layout, color psychology, lighting, and sound, this study aims to uncover how these elements can be strategically applied to create engaging and effective retail environments. Two case studies, Westside and Shopper’s Stop at Phoenix Palassio, are examined to demonstrate the practical application of these principles. The findings reveal that thoughtfully designed store layouts significantly impact consumer movement and engagement, with free-flow layouts promoting exploration and racetrack layouts ensuring comprehensive product exposure. The strategic use of different colors creates an impact on consumer purchasing power. Proper lighting enhances product appeal and creates a welcoming atmosphere, while carefully selected music and controlled ambient noise contribute to a positive shopping experience. The study aligns with existing research, highlighting the importance of psychological principles in retail design. However, it also identifies areas for further investigation, including cultural variations, technological integration, long-term impacts, and sustainability. Practical recommendations for retail designers and managers are provided, emphasizing the optimization of store layouts, strategic use of colors, effective lighting design, and incorporation of sound and music to enhance consumer experience. This research underscores the significance of integrating psychological insights into retail interior design to create environments that attract customers, foster positive shopping behaviors, and drive business success. Future research tends to explore new trends and technologies to create an engaging retail design.
Keywords: Lighting; color psychology; scent marketing; sound and music; store layout; visual merchandising